A hepatitis B virus core antigen‐based virus‐like particle vaccine expressing SARS‐CoV‐2 B and T cell epitopes induces epitope‐specific humoral and cell‐mediated immune responses but confers limited protection against SARS‐CoV‐2 infection. Issue 2 (26th January 2023) - Hassebroek, Anna M.; Sooryanarain, Harini; Heffron, Connie L.; Hawks, Seth A.; LeRoith, Tanya; Cecere, Thomas E.; Stone, William B.; Walter, Debra; Mahsoub, Hassan M.; Wang, Bo; Tian, Debin; Ivester, Hannah M.; et al.
Abstract: The hepatitis B virus core antigen (HBcAg) tolerates insertion of foreign epitopes and maintains its ability to self‐assemble into virus‐like particles (VLPs). We constructed a ∆HBcAg‐based VLP vaccine expressing three predicted severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) B and T cell epitopes and determined its immunogenicity and protective efficacy. The recombinant ∆HBcAg‐SARS‐CoV‐2 protein was expressed in Escherichia coli, purified, and shown to form VLPs. K18‐hACE2 transgenic C57BL/6 mice were immunized intramuscularly with ∆HBcAg VLP control ( n  = 15) or ∆HBcAg‐SARS‐CoV‐2 VLP vaccine ( n  = 15). One week after the 2nd booster and before virus challenge, five ∆HBcAg‐SARS‐CoV‐2 vaccinated mice were euthanized to evaluate epitope‐specific immune responses. There is a statistically significant increase in epitope‐specific Immunoglobulin G (IgG) response, and statistically higher interleukin 6 (IL‐6) and monocyte chemoattractant protein‐1 (MCP‐1) expression levels in ∆HBcAg‐SARS‐CoV‐2 VLP‐vaccinated mice compared to ∆HBcAg VLP controls. While not statistically significant, the ∆HBcAg‐SARS‐CoV‐2 VLP mice had numerically more memory CD8+ T‐cells, and 3/5 mice also had numerically higher levels of interferon gamma (IFN‐γ) and tumor necrosis factor (TNF). After challenge with SARS‐CoV‐2, ∆HBcAg‐SARS‐CoV‐2 immunized mice had numerically lower viral RNA loads in the lung, and slightly higher survival, but the differences are not statistically significant. These results indicate that the ∆HBcAg‐SARS‐CoV‐2 VLP vaccine elicits epitope‐specific humoral and cell‐mediated immune responses but they were insufficient against SARS‐CoV‐2 infection.